INCREASING THE EFFICIENCY OF THE LOADER WITH A HYDRAULIC DRIVE OF THE CUTTING MECHANISM FOR UNLOADING SILAGE FROM TRENCH STORAGE - RUTKEVYCH, VOLODYMYR; OSTAPENKO, ALEXEI; ZALOGIN, RUSLAN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The question of improving the efficiency of technical means for unloading stalk fodder - silage from trench storages is under consideration. The importance of complying with agro-zootechnical requirements when separating the block portion from the fodder monolith is indicated, which will lead to an increase in quality and nutritional value of stem fodder for animals. The advantages and disadvantages of existing technical means for the technological operations of unloading stem fodder from trench storages are considered. Modern trends in the development of technological equipment for animal husbandry were noted, and it was established that an increase in energy and technological indicators is possible by hydrofication of the drives of the working bodies of the equipment, including cutting mechanisms for unloading silage from trenches storage It is noted that the operation of the hydraulic drive of most working bodies is accompanied by shock loads and oscillating processes associated with both the occurrence of significant pressure fluctuations and the flow of the working fluid, as well as the consequence of the technical imperfection of the schematic design solution of the hydraulic drive. Oscillating processes have a negative effect on the resource of the hydraulic drive, reduce the utilization ratio of the set power of the drive and productivity, reduce reliability, and increase the energy consumption of the drive and the machine as a whole. A fundamentally new structural and technological scheme is proposed cutting mechanism for unloading silage from trench storages with hydraulic drive of working bodies. The developed structure of the hydraulic drive of the cutting mechanism is adapted to changes in the technological load on the working bodies, which allows to coordinate the modes of operation of the cutting mechanism and to correspond to modern, innovative approaches to creating resource-saving and energy-efficient equipment for animal husbandry.